Evaluation of Foetal Modified Myocardial Performance Index as a Predictor of Perinatal Outcome in Intrauterine Growth Restriction Foetuses: A Prospective Cohort Study - Sinddhu Mani; Ramachandran Palanisamy; Veeraraghavan Gunasekaran; Subhashree Chandrasekaran; Murali Nanjundan (Journal of Clinical and Diagnostic Research)
Introduction: Functional cardiovascular assessment is gaining significance as a key tool in understanding foetal pathology. The foetal Modified Myocardial Performance Index (Mod-MPI) is a non invasive, pulsed-wave Doppler-derived measure of global cardiac function. Mod-MPI is independent of ventricular size, geometry and heart rate. Despite advances in the diagnosis and management of Intrauterine Growth-Restricted foetuses (IUGR), there remains a small proportion of cases that face severe adverse perinatal outcomes despite normal conventional Doppler studies. This highlights the need for new indices such as Mod-MPI for improved perinatal outcomes. Aim: To assess foetal cardiac function using Mod-MPI in IUGR foetuses in the third trimester and to compare Mod-MPI values with those of normal controls. Materials and Methods: The prospective cohort study was conducted in the Department of Radiology at Government Coimbatore Medical College Hospital, Coimbatore, Tamil Nadu, India, from May 2024 to December 2024. A total of 43 singleton pregnancies in the third trimester with IUGR (cases) and 43 gestational age-matched normal singleton pregnancies in the third trimester (controls) were included in the study and were followed until delivery. The Mod-MPI was calculated in the foetal left ventricle by placing the Doppler sample in the internal leaflet of the mitral valve and estimating three time periods: Isovolumetric Contraction Time (ICT), Isovolumetric Relaxation Time (IRT) and Ejection Time (ET). The Mod-MPI was calculated as (ICT+IRT)/ET. Independent sample t-tests and Chi-squared tests were used for comparison between cases and controls. Results: The mean Mod-MPI value in the control group was found to be 0.41, with a Standard Deviation (SD) of 0.05. In IUGR cases, the mean Mod-MPI value was found to be 0.56±0.06. The p-value was <0.001. Based on the results, a value of 0.4950 was taken as a cut-off in the present study for the occurrence of adverse perinatal outcomes. Moreover, IUGR foetuses with higher left Mod-MPI values were associated with significantly worse perinatal outcomes and increased morbidity compared to the control group and IUGR foetuses with normal Mod-MPI values. Conclusion: The Mod-MPI is a simple and sensitive parameter for early foetal cardiac adaptation and higher MPI values were significantly associated with adverse perinatal outcomes, even in the presence of normal conventional Doppler findings.